2001
DOI: 10.3998/ark.5550190.0002.214
|View full text |Cite
|
Sign up to set email alerts
|

The Biginelli dihydropyrimidone synthesis using polyphosphate ester as a mild and efficient cyclocondensation/dehydration reagent

Abstract: Dedicated to Professor Fritz Sauter on the occasion of his 70th birthday (received 16 Jan 01; accepted 30 Oct 01; published on the web 07 Nov 01) Abstract 4-Aryldihydropyrimidine-2-(1H)-ones 4a-z were synthesized by one-pot, polyphosphate estermediated Biginelli three-component condensation. The yields of dihydropyrimidones obtained via this novel protocol are significantly higher than those utilizing the conventional ethanol/HCl method. The mechanism of the polyphosphate ester based method and the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 7 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Results are given in Tables 4 and 5. A comparison with modern classic synthetic methods for dihydropyrimidinones and dihydropyridines [31,32] gives very good parameters (Figures 4 and 5).…”
Section: Synthesis Of 13-dihydropyrimidinonesmentioning
confidence: 92%
“…Results are given in Tables 4 and 5. A comparison with modern classic synthetic methods for dihydropyrimidinones and dihydropyridines [31,32] gives very good parameters (Figures 4 and 5).…”
Section: Synthesis Of 13-dihydropyrimidinonesmentioning
confidence: 92%
“…In 2001, Falsone and Kappeexplored the Biginelli reaction conditions and reported the polyphosphate ester (PPE) mediated condensation between ethyl acetoacetate 6, benzaldehydes 7, and urea 8 to achieve pyrimidin-2-ones 9 in good to excellent yields (Scheme 1). 14 It was observed that the use of PPE in THF solvent stabilized the N -acyliminium ion intermediates produced during the Biginelli reaction. Bicyclic 6-6 fused ring systems are well known due to their potent antipsychotic, analgesic, and antiasthmatic properties.…”
Section: Multicomponent Synthesismentioning
confidence: 99%
“…The synthetic methodology used to create dipyrimidines has been well attested and has typically involved variations of the original Biginelli reaction [13][14][15][16]. However, this reaction often requests long reaction time, rough conditions, and affords low yield, particularly when substituted aliphatic and aromatic aldehydes are used.…”
Section: Introductionmentioning
confidence: 99%